(untitled) (The Pakistan Development Review, 1998)
The importance of agriculture in the economy of Pakistan is well established. Agricultural plays an important role both directly and indirectly in generating economic activity, growth and development. Agriculture has strong backward and forward linkages and is vital to the food security of the country. Fertilisers have played an important role in Pakistan agriculture particularly in meeting the growing demand for food grains, fibre, fuel and fodder. Fertiliser consumption has increased during the last four decades to 2.6 million tonnes by 1997-98. The use level is, however, not only sub optimal but also imbalanced. Better plant nutrient management is, therefore, necessary for achieving self reliance in agriculture.